Relating elasticity and graphene folding conformation. Issue 71 (2nd August 2015) - Cox, Barry J.; Baowan, Duangkamon; Bacsa, Wolfgang; Hill, James M.
<x xml:space="preserve">Abstract</x> Variational calculus is employed to determine the folding behaviour of a single graphene sheet.